An Approach of Good Governance- Based Administration for Phrapariyattidhamma Schools, General Education Division in Kalasin Province - Sumangalo(Phuprathan), Phraphichan; Phrakhruvichitpanyaporn; Phrakruchairattanagon (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study the situation of an approach of good governance-based administration for Phrapariyattidhamma Schools, general education division in Kalasin province, 2) to compare the so-said administration Phrapariyattidhamma Schools, general education division in Kalasin province, classified by gender, age and education, 3) to compile the related recommendations as suggested for Phrapariyattidhamma Schools, general education division in Kalasin province. The population consisted of the staff members of those schools, totally 109 in number. The device used to collect the information was the five-rating scale. The statistics used in this research are percentage, mean, standard deviation, and examining the hypothesis by using t-test and F-test(One-way ANOVA) statistics by using a package program. The research found that: 1. The situation of the good governance-based administration for Phrapariyattidhamma schools general education division in Kalasin province was, in an overall aspect, found to stand at the ‘MUCH’ level. In an individual aspect, the item that was ranked on top of the scale in terms of mean was the rule of law, followed by morality, transparency, cost-coverage, participation and accountability, respectively. 2. The comparison of the so-said administration classified by gender was, in both overall and individual aspects, found no difference, but the comparison by age and education in almost all aspects displayed no difference, except in the aspect of transparence where it showed the statistically significant difference at .05. 3) Suggestions on academic administration according to the good governance of the Phrapariyattidhamma school, general department, Kalasin province Executives provide opportunities for personnel to participate in the planning, and set school policies administrative administration finance, budget, supplies and accountability.